Training On Making Roll-On Aromatherapy Of Calamansi Orange Essential Oil In Pondok Kubang Sub-District, Central Bengkulu - Purnama, Yetti; Dewiani , Kurnia; Yusanti, Linda; Rahmawati, Suci; Pratama, Rini Mustikasari Kurnia; Damayanti (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2023)
Calamansi orange (Citrofortunella microcarpa) is one of the commodities that has been developed and processed into calamansi orange syrup. One of the by-products of the calamansi orange syrup industry is peel. Calamansi orange peel contains a lot of essential oils, the use of which can be made in the form of aromatherapy roll-on preparations. One of the essential oil contents of calamansi orange is decanal. Decanal in aromatherapy causes a feeling of relaxation. The aim of this service is to train the community on how to make calamansi orange essential oil aromatherapy in roll on packaging form at MSMEs Bukit Bengkulu, Pondok Kubang Sub-District, Central Bengkulu. The community service method is in the form of training on making essential oil from Calamansi orange peel and making preparations in the form of roll-on for aromatherapy using leaflets, tools and materials that have been prepared, the number of participants is 15 peoples. The service team carried out a demonstration and then were given the opportunity to demonstrate one by one. The results of this training show that the participants have the skills to make calamansi essential oil with an average score of 83 and have the skills to make roll on essential oil for calamansi orange peel, namely an average score of 87, exceeding the target of 80. The results of this training show an increase in participants’s skills in making essential oils and calamansi orange peel aromatherapy roll-on which can be used as aromatherapy and increase community income through MSMEs.